113k views
2 votes
The graph of g(x) is the result of translating the graph of f(x) = (one-half) Superscript x three units to the left. What is the equation of g(x)? g(x) = (one-half) Superscript x minus 3 g(x) = (one-half) Superscript x + 3 g(x) = (one-half) Superscript x Baseline minus 3 g(x) = (one-half) Superscript x Baseline + 3

User FireGM
by
5.3k points

2 Answers

7 votes

Answer:

In the case of exponential functions, the graph is shifted when a constant is added to the exponent of the constant. The original equation, f(x) is:

f(x) = (1/2)ˣ

Now, when horizontal shifting is occurring, the equation is:

y = Cˣ⁺ᵃ

If a is positive, the graph shifts to the lefts and the shift is equal to a units. If a is negative, the graph shifts to the right and the shift is equal to a units. Therefore, to shift the graph 3 units to the left

Explanation:

g(x) = (1/2)⁽ˣ⁺³⁾

User Buneme Kyakilika
by
5.6k points
4 votes

Answer:

B B B B B B B

Explanation:

B is the answer if you are in a hurry

User Erik I
by
5.1k points